2021
DOI: 10.3390/biomedicines9070773
|View full text |Cite
|
Sign up to set email alerts
|

Association between Blood Pressure, Blood Pressure Variability, and Post-Stroke Cognitive Impairment

Abstract: After stroke, dynamic changes take place from necrotic-apoptotic continuum, inflammatory response to poststroke neurogenesis, and remodeling of the network. These changes and baseline brain pathology such as small vessel disease (SVD) and amyloid burden may be associated with the occurrence of early or late poststroke cognitive impairment (PSCI) or dementia (PSD), which affect not only stroke victims but also their families and even society. We reviewed the current concepts and understanding of the pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 236 publications
0
6
0
2
Order By: Relevance
“…Mechanism linking diabetes mellitus and PSCI/dementia A previous review demonstrated that PSCI depends on multiple factors, including the location of the stroke, duration of the initial inflammatory response, late aberrant neurogenesis, and baseline brain pathologies. 7 The activation of microglia seems to play an important role in the inflammatory response. 8 Chronic hyperglycemia leads to pro-inflammatory microglial proliferation via the endothelin-1 system.…”
Section: Diabetes Mellitus and Psci/post-stroke Dementia (Psd)mentioning
confidence: 99%
“…Mechanism linking diabetes mellitus and PSCI/dementia A previous review demonstrated that PSCI depends on multiple factors, including the location of the stroke, duration of the initial inflammatory response, late aberrant neurogenesis, and baseline brain pathologies. 7 The activation of microglia seems to play an important role in the inflammatory response. 8 Chronic hyperglycemia leads to pro-inflammatory microglial proliferation via the endothelin-1 system.…”
Section: Diabetes Mellitus and Psci/post-stroke Dementia (Psd)mentioning
confidence: 99%
“…Beyond modifying average BP levels, there has been recent interest in BP variability (BPV) as a risk factor for dementia, in part due to BP's highly variable nature and its potential therapeutic implications [5][6][7][8] . Emerging evidence suggests elevated BPV over the longer term (e.g., over months to years or "visit-to-visit" BPV) and shorter term (e.g., over minutes, days) is associated with cognitive impairment and decline 8 , incidence and progression of dementia, including AD and vascular dementia 7,[9][10][11][12] , cerebrovascular disease [13][14][15] , stroke 16,17 , and AD pathology 18 , independent of average BP levels 8 . Further evidence indicates these relationships may be especially pronounced in individuals at increased genetic risk for AD through the apolipoprotein (APOE) e4 allele [19][20][21] .…”
mentioning
confidence: 99%
“…Post-stroke cognitive impairment (PSCI) is one of the most prevalent stroke consequences, and it can have a detrimental impact on the rehabilitation of stroke patients’ athletic function, daily living abilities, and a financial burden 1 . Stroke survivors may experience a decline in cognitive function and neuropsychiatric symptoms in a short period after stroke 2 . The previous study had demonstrated that the cognitive function in the initial 2 weeks (acute phase) can predict significant cognitive impairment 3 - 6 months after stroke 3 .…”
Section: Introductionmentioning
confidence: 99%